Are project managers ready for the 21th challenges? A review of problem structuring methods for decision support - San Cristóbal Mateo, José Ramón (2022)
Numerous contemporary problems that project managers face can be considered as unstructured decision problems, characterized by multiple actors and perspectives, incommensurable and/or conflicting objectives, and important intangibles. This work environment demands that project managers to possess not only hard skills but also soft skills with the ability to take a management perspective and, above all, develop real leadership capabilities. In this paper, is presented a family of problem structured methods for decision support, aimed at assisting project managers in tackling complex problems. Problem structured methods are a family of soft operations research methods for decision support that assist groups of diverse composition to agree on a problem focus and make commitments to consequential action. Project management programs are challenged to implement these methodologies in such a way that it is organized around the key competences that a project manager needs in order to be more effective, work efficiently as members of interdisciplinary teams and successfully execute even a small project.